The nexus of government incentives and sustainable development goals: is the management of resources the solution to non-profit organisations? - Anwar, Muhammad; Khattak, Muhammad Sualeh; Popp, József; Meyer, Daniel Francois; Máté, Domicián (Technological and Economic Development of Economy, 2020)
Sustainable Development Goals (SDGs) have become the main priority across the globe due to their significant role in economic growth and propensity. However, in particular, it is not yet known how governments can achieve SDGs through non-profit organisations (NPOs) by providing financial and non-financial incentives. The present study included 263 Pakistan NPOs in a primary survey using a questionnaire. The results obtained from the Structural Equation Modelling (SEM) highlight that: (i) government incentives do not directly influence community development; (ii) The government non-financial incentives have a significant direct effect on environmental activities to reduce pollution, energy consumption and waste; (iii) Resource management fully mediates the paths between government incentives and community development while partially mediates environmental activities; and finally, (iv) resource management has a favourable influence both on the goals of community development and environmental activities. This research paper contributes to the knowledge in that government incentives do not have a direct influence on social development, but has an indirect influence through efficient management. Recommendations are that government and public bodies need to support NPOs to engage actively in philanthropic activities. Similarly, NPOs should efficiently utilize and manage the resources to benefit the maximum number of poor and needy individuals.First published online 22 September 2020